The 3D-Printing Technology to produce temporary motorcycle handle grip using PLA - Chang, Wai Kin; Salleh, Mohamed Najib (Universiti Utara Malaysia, 2020)
3D printing also known as additive manufacturing means three-dimensional printing. This experiment will study whether 3D printing technology is suitable to create temporary motorcycle handle grip, to examine the durability of PLA filament and study whether PLA filament is suitable to be used for printing temporary handle grip. This experiment had used 3D printer, computer software, PLA filament and actual handle grips. The experiment also determine that PLA has good durability and it is suitable for printing temporary handle grip. 3D printing technology can replace the current technology as it is very convenient and easy to be used.